Corrosion behavior of T91 tubing in high temperature supercritical carbon dioxide environment. (February 2023) - Gui, Yong; Liang, Zhiyuan; Wang, Shuo; Zhao, Qinxin
Abstract: The effect of stress on the corrosion behavior and mechanical properties of T91 tube exposed to high-temperature supercritical carbon dioxide (S-CO2 ) was investigated. Both yield strength, ultimate tensile strength, and elongation of T91 tube was decreased after being exposed to S-CO2 . Besides, a large number of carbide precipitates were observed in the Fe-Cr-rich corrosion layer of T91 tube, which was attributed to higher ion diffusion and carburizing rate under the action of stress. As a result, the corrosion rate of T91 tube was significantly faster than that of T91 coupon. Highlights: The effect of stress on the corrosion behavior and mechanical properties of T91 tube exposed to high-temperature S-CO2 environment was investigated. With the action of stress, the corrosion rate of T91 tube was significantly faster than that of T91 coupon under the same condition. Both yield strength, ultimate tensile strength, and elongation of T91 tube was decreased after being exposed to S-CO2 . A large number of carbide precipitates were observed in the Fe-Cr-rich corrosion layer of T91 tube, which was attributed to a higher carburizing rate.